Auditor Ethics as the Foundation of Audit Quality: A Systematic Literature Review (Pusat Riset dan Inovasi Nasional, 2026)
This study presents a comprehensive Systematic Literature Review (SLR) on the crucial role of auditor ethics as the foundation of audit quality. The primary objective of this SLR is to thoroughly examine existing literature and identify the relationship between dimensions of auditor ethics including moral values, integrity, objectivity, independence, and professional skepticism and audit quality. The research methodology used in this study is SLR, involving systematic searching, critical selection, and synthesis of findings from 20 empirical articles published between 2019–2025. The literature sources were accessed through leading academic databases such as Scopus, Web of Science, Sinta, and JSTOR by using relevant keywords such as “auditor ethics” and “audit quality.” The findings consistently indicate that auditor ethics has a significant and positive effect on audit quality. Auditors who uphold ethical values, supported by a strong organizational culture, professional commitment, and internal locus of control, significantly contribute to the improvement of audit quality. This study also highlights that ethics is a necessary but not sufficient factor and is strengthened by various supporting factors as well as influenced by organizational and situational contexts. The originality of this study lies in its structured synthesis of recent literature, which not only confirms the positive effect of auditor ethics but also elaborates key mechanisms, moderating factors, and identifies critical research gaps for future studies. The results of this SLR provide significant theoretical and practical implications for the development of the auditing profession and accounting education.